Inflammatory nociception diminishes dopamine release and increases dopamine D2 receptor mRNA in the rat's insular cortex - Amaya María; Jaimes Orlando; Simón-Arceo Karina; de Gortari Patricia; Ortega-Legaspi J; Coffeen Ulises; Pellicer Francisco (SAGE Publishing, 2010)
Abstract Background The insular cortex (IC) receives somatosensory afferent input and has been related to nociceptive input. It has dopaminergic terminals and D1 (D1R) -excitatory- and D2 (D2R) -inhibitory- receptors. D2R activation with a selective agonist, as well as D1R blockade with antagonists in the IC, diminish neuropathic nociception in a nerve transection model. An intraplantar injection of carrageenan and acute thermonociception (plantar test) were performed to measure the response to inflammation (paw withdrawal latency, PWL). Simultaneously, a freely moving microdyalisis technique and HPLC were used to measure the release of dopamine and its metabolites in the IC. Plantar test was applied prior, one and three hours after inflammation. Also, mRNA levels of D1 and D2R's were measured in the IC after three hours of inflammation. Results The results showed a gradual decrease in the release of dopamine, Dopac and HVA after inflammation. The decrease correlates with a decrease in PWL. D2R's increased their mRNA expression compared to the controls. In regard of D1R's, there was a decrease in their mRNA levels compared to the controls. Conclusions Our results showed that the decreased extracellular levels of dopamine induced by inflammation correlated with the level of pain-related behaviour. These results also showed the increase in dopaminergic mediated inhibition by an increase in D2R's and a decrease in D1R's mRNA. There is a possible differential mechanism regarding the regulation of excitatory and inhibitory dopaminergic receptors triggered by inflammation.